Protection of TPKS Victims Through the Compensation Mechanism and Victim Assistance Funds in Government Regulation No. 29 of 2025 - Putri Ayu Lennas; Siska Karina; Ismayana Ismayana (International Journal Labs, 2026)
This study investigates the protection of victims of sexual violence through the compensation mechanism and the Victim Assistance Fund (DBK) as regulated in Government Regulation No. 29 of 2025 in Indonesia. Despite legal recognition of restitution as a victim’s right, implementation remains constrained by perpetrators’ financial capacity, insufficient inter-institutional coordination, and procedural complexities, leaving many victims without effective recovery. The study aims to analyze the mechanisms for compensation, identify operational and structural obstacles, and assess the effectiveness of DBK as a state-guaranteed alternative for victim recovery. A normative juridical approach was employed, combining legal and conceptual analyses, with data collected through statutory review, document analysis, and structured interviews with relevant stakeholders. The results indicate that while restitution mechanisms have been integrated from the investigation stage, their effectiveness is limited due to dependence on perpetrators’ ability to pay. Furthermore, DBK, designed to ensure recovery independent of the perpetrator, has not been operationally implemented at the regional level, constrained by unclear technical procedures, budget limitations, and weak coordination. The findings highlight a gap between legal design and practical execution, confirming that victim protection is still largely normative. The study concludes that strengthening institutional integration, operational clarity, and resource allocation for DBK is critical to provide real, sustainable recovery for victims and enhance the victim-oriented criminal justice system in Indonesia.